Beeswax Luminaires: Sustainable lighting through materials design - Junpyo Kwon; Pelin Asa; Mourad Jaffar-Bandjee; Shahrouz Amini; Peter Fratzl; Karola Dierichs (Materials & Design)
Biogenic materials like beeswax have potential for sustainable manufacturing by reducing environmental impact. This study introduces “Beeswax Luminaires”, a sustainable lighting solution made from natural beeswax and water via ice-casting. The objectives are to characterize beeswax properties, optimize luminaire design for mechanical strength and light diffusion, and develop scalable robotic fabrication. Results indicate that beeswax maintains rigidity up to 50°C and possesses suitable translucency for lighting. Parametric modeling produced corrugations enhancing flexural rigidity and light diffusion uniformity. Robotic fabrication precisely controlled coating thickness and quality, reducing product defects. Life-cycle assessment showed the production was energy-efficient, consuming less energy than traditional methods. These findings support Beeswax Luminaires as an eco-friendly lighting option, combining sustainability, optimized design and efficient manufacturing.